Key challenges and critical success factors for the Islamic banking sector of Bangladesh - Tanny, Mohibba Tabassum; Islam, rafikul; Wan Husain, Wan Rohaida (Department of Shariah and Management, Academy of Islamic Studies, Universiti Malaya, 2025)
This research investigates the challenges faced by Islamic banks in Bangladesh in delivering quality service and identifies the critical success factors (CSFs) needed to overcome those obstacles. Semi-structured online interviews were conducted with a purposive sample of 15 experienced bankers from Islamic banks across Bangladesh. Most participants have over 18 years of experience in the field, and their insights offer valuable perspectives on macro and microeconomic challenges. The qualitative analysis of the interviews highlighted five significant challenges and 29 related CSFs. Key challenges include inadequate governance, limited access to capital markets and financial investment, liquidity issues, a lack of Islamic banking products and services, and employees' need for more knowledge about Islamic banking. Understanding these challenges and their CSFs can facilitate Islamic banks in effectively allocating resources, improving their operational performance, and achieving a sustainable competitive advantage. This, in turn, can pave the way for a brighter, more prosperous future for Islamic banking in Bangladesh. By implementing these strategic interventions, Islamic banks can strengthen their role in the wider economic landscape, promoting a more prosperous future for the industry.